Tutorial on interpreting x-ray photoelectron spectroscopy survey spectra: Questions and answers on spectra from the atomic layer deposition of Al2O3 on silicon - Shah, Dhruv; Patel, Dhananjay I.; Roychowdhury, Tuhin; Rayner, G. Bruce; O’Toole, Noel; Baer, Donald R.; Linford, Matthew R. (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2018)
X-ray photoelectron spectroscopy (XPS) has become the most widely used method for chemically analyzing surfaces. In XPS, photoelectrons are generated by irradiating a surface with x rays. As the importance and popularity of XPS have grown, it has drawn users without significant XPS experience, and incorrect and incomplete interpretations of XPS spectra regularly appear in the literature. This tutorial is designed as a tool to guide less experienced users in analyzing XPS survey spectra. Here, the authors examine a series of XPS survey spectra collected during the atomic layer deposition (ALD) of Al2O3 from trimethylaluminum and water precursors. Prior to this, brief explanations of XPS and ALD are presented. This tutorial is structured as a series of questions and answers that the interested reader may choose to engage in. The XPS spectra are scrutinized to extract information about the elements present in the film, the presence of contamination, and the nature of the film growth process. The questions and answers in this tutorial address important fundamental issues common to the interpretation of many XPS survey spectra in the context of ALD.